Peramalan Jumlah Konsumsi Daging Sapi Indonesia Dengan Menggunakan Metode ARIMA - M Fathoni Arnas; Helma Helma; Yenni Kurniawati (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Each year the consumption of beef in Indonesia is rising, but not followed by the high production of beef in the country. A shortage of beef production which cause the price of beef rises so it can’t beef affordable of society. Therefore be required estimate to amount of beef consumption in Indonesia. This is useful so that the Government can estimate of the consumption of beef is coming so that the Government try to satisfy the supply of beef consumption. One Forecasting method of used is ARIMA method. That formulation of the problem is